Sodium nitroprusside enhanced cardiopulmonary resuscitation improves short term survival in a porcine model of ischemic refractory ventricular fibrillation. (January 2017) - Yannopoulos, Demetris; Bartos, Jason A.; George, Stephen A.; Sideris, George; Voicu, Sebastian; Oestreich, Brett; Matsuura, Timothy; Shekar, Kadambari; Rees, Jennifer; Aufderheide, Tom P.
Abstract: Introduction: Sodium nitroprusside (SNP) enhanced CPR (SNPeCPR) demonstrates increased vital organ blood flow and survival in multiple porcine models. We developed a new, coronary occlusion/ischemia model of prolonged resuscitation, mimicking the majority of out-of-hospital cardiac arrests presenting with shockable rhythms. Hypothesis: SNPeCPR will increase short term (4-h) survival compared to standard 2015 Advanced Cardiac Life Support (ACLS) guidelines in an ischemic refractory ventricular fibrillation (VF), prolonged CPR model. Methods: Sixteen anesthetized pigs had the ostial left anterior descending artery occluded leading to ischemic VF arrest. VF was untreated for 5 min. Basic life support was performed for 10 min. At minute 10 (EMS arrival), animals received either SNPeCPR (n = 8) or standard ACLS (n = 8). Defibrillation (200J) occurred every 3 min. CPR continued for a total of 45 min, then the balloon was deflated simulating revascularization. CPR continued until return of spontaneous circulation (ROSC) or a total of 60 min, if unsuccessful. SNPeCPR animals received 2 mg of SNP at minute 10 followed by 1 mg every 5 min until ROSC. Standard ACLS animals received 0.5 mg epinephrine every 5 min until ROSC. Primary endpoints were ROSC and 4-h survival. Results: All SNPeCPR animals (8/8) achieved sustained ROSC versus 2/8 standard ACLS animals within one hour of resuscitation (p = 0.04). The 4-h survival was significantly improved with SNPeCPR compared to standard ACLS, 7/8 versus 1/8 respectively, p = 0.0019. Conclusion: SNPeCPR significantly improved ROSC and 4-h survival compared with standard ACLS CPR in a porcine model of prolonged ischemic, refractory VF cardiac arrest.